Preparation method of fine-grained low-oxygen molybdenum-silicon-boron alloy based on molten salt method
The preparation of Mo-Si-B alloys by molten salt method solves the oxidation and agglomeration problems in powder metallurgy technology, achieves high-performance fine crystal structure and optimized mechanical properties, and significantly improves the compressive strength and fracture toughness of the alloy.
Patent Information
- Application Number
- CN202310061195.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-01-19
AI Technical Summary
The existing powder metallurgy technology can easily lead to oxidation and agglomeration of the precursor powder when preparing Mo-Si-B alloys, resulting in uneven alloy structure and high oxygen content, affecting its mechanical properties.
The fine crystalline low-oxygen Mo-Si-B alloy was prepared by molten salt method, and then mixed by ball milling and pressing and calcining under the CaCl2 salt medium to remove oxygen impurities and achieve the formation of a uniform fine crystal structure.
It effectively reduces the oxygen content and agglomeration phenomenon in Mo-Si-B alloy, optimizes its microstructure and mechanical properties, and improves the compressive strength and fracture toughness in room temperature.
Smart Images

Figure CN116179880B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of refractory metal materials, and in particular relates to a method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method. Background Art
[0002] Nickel-based superalloys are the main materials for aircraft engine blades at present. Their service temperature is close to 1150℃, reaching 90% of their own melting point. At the same time, with the rapid development of the aerospace industry, in order to further improve the efficiency of aircraft engines and obtain higher thrust-to-weight ratios, the gas temperature and pressure in the combustion chamber are constantly increasing. Although the use of complex cooling systems and thermal barrier coatings can improve the temperature of the hottest area of turbine engines (about 1500℃), nickel-based superalloys can be used to resist the temperature of the hottest area of turbine engines. However, the use of forced air cooling and coatings greatly reduces the performance and efficiency of the engine at high temperatures. Therefore, the design and preparation of new high-temperature structural materials that do not require cooling systems to replace nickel-based superalloys have attracted widespread attention at home and abroad. Mo-Si-B alloy has an ultra-high melting point (>2000℃), excellent high-temperature strength and high-temperature creep resistance, and still has good oxidation resistance at temperatures above 1300℃. Therefore, Mo-Si-B alloy is expected to become the material used for the hot end components of the next generation of aircraft engines.
[0003] Mo-Si-B alloy is mainly composed of three phases: α-Mo, Mo3Si and Mo5SiB2. Studies have shown that when the alloy microstructure shows the fine-grained structure characteristics of α-Mo, Mo3Si and Mo5SiB2 with uniform distribution, the alloy can obtain good comprehensive properties. The significant room temperature strengthening and toughening effect of the fine-grained structure optimizes the room temperature strength and fracture toughness of the alloy. At the same time, a large number of grain boundaries in the fine-grained structure at high temperature become fast diffusion channels for Si and B atoms, accelerating the formation of a protective and self-healing borosilicate passivation layer on the alloy surface, greatly improving the high-temperature oxidation resistance of the alloy. In terms of alloy preparation technology, powder metallurgy is a common method for preparing fine-grained Mo-Si-B alloys. It can not only minimize the segregation of alloy components, but also achieve precise control of the bulk alloy structure by changing the size and structure of the precursor powder. In the process of precursor powder preparation, mechanical alloying treatment is usually selected to refine the powder particles and realize the pre-alloying of alloy elements, thereby promoting the acquisition of fine-grained structure of the bulk alloy after sintering. However, during the mechanical alloying process, on the one hand, the alloy powder is easy to agglomerate, resulting in uneven alloy structure after sintering; on the other hand, due to the high surface energy of the powder, it is easy to adsorb oxygen impurities, resulting in an oxygen impurity content of up to 1.2wt% to 1.5wt% in the alloy. Based on thermodynamic research, it is confirmed that the most active Si element in the alloy usually reacts with O first to form SiO2 and is concentrated at the grain boundaries of the alloy (SiO2 content is 7 to 9vol.%). This will not only affect the main phase composition and content of the alloy, but also reduce the room temperature / high temperature mechanical properties of the alloy. Therefore, exploring new technical processes to obtain precursor powders with fine particles, uniform distribution and low oxygen content has become a key issue that needs to be solved in the preparation of high-performance Mo-Si-B alloys by powder metallurgy. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method, which solves the problems of oxidation and agglomeration of Mo-Si-B precursor powders that are easily caused by existing powder metallurgy technology, thereby optimizing the organizational uniformity of the molybdenum-silicon-boron alloy and improving the mechanical properties of the alloy.
[0005] The technical solution adopted by the present invention is a method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method, which is specifically implemented according to the following steps:
[0006] Step 1, ball-milling molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol to obtain a uniformly mixed slurry;
[0007] Step 2, drying the mixed slurry obtained in step 1 to obtain a mixed powder;
[0008] Step 3: Press the mixed powder obtained in step 2 into The small cylindrical green compact is then placed into In the tableting mold, fill the small cylindrical green body with CaCl2 salt and press it again. Large cylindrical green compact;
[0009] Step 4: The large cylindrical compact obtained in step 3 is heated and calcined from room temperature to obtain a loose block; Step 5: The loose block taken out after calcination is washed and filtered to remove CaCl2 salt, and then dried and ground to obtain Mo-Si-B precursor powder;
[0010] Step 6: The Mo-Si-B precursor powder obtained in step 5 is heated from room temperature to 1550-1700°C and then hot-pressed and sintered. The powder is then depressurized and cooled in the furnace before being taken out to obtain a fine-grained low-oxygen Mo-Si-B alloy.
[0011] The present invention is also characterized in that:
[0012] In step 1, the mass percentage of molybdenum powder is 93.0%-95.0%, the mass percentage of silicon powder is 4.0%-5.0%, and the mass percentage of boron powder is 1.0%-2.0%, and the sum of the above mass fractions is 100%; the purity of the molybdenum powder is ≥99.9%, and the particle size of the molybdenum powder is <5μm; the purity of the silicon powder is ≥99.99%, and the particle size of the silicon powder is <5μm; the purity of the boron powder is ≥99.95%, and the particle size of the boron powder is <1μm; the mass ratio of the CaCl2 salt to the total of the molybdenum powder, silicon powder and boron powder is (1-2): 1, the purity of the CaCl2 salt is ≥99.9%, and the particle size of the CaCl2 salt is <5μm; the volume of the anhydrous ethanol is 1 / 4-1 / 2 of the total volume of the molybdenum powder, silicon powder, boron powder and CaCl2 salt.
[0013] In step 1, the ball milling time is 6h-10h, the ball-to-material ratio is (1-2):1, the ball milling speed is 200r / min-400r / min, and Ar gas atmosphere is introduced during the ball milling process, and the gas pressure in the ball mill is 0.3MPa-0.6MPa.
[0014] In step 2, the drying temperature is 200°C-500°C, and the drying time is 5h-10h.
[0015] The pressure during the powder pressing process in step 3 is 25MPa to 37MPa.
[0016] In step 4, the mixture is heated from room temperature to 1000°C-1400°C, calcined for 1-2 hours, and then cooled to room temperature in the furnace to obtain a loose block. The heating rate during the calcination process is 5-10°C / min, the vacuum degree in the furnace is ≤5Pa, and the mixture is cooled to room temperature in the furnace after the calcination.
[0017] In step 5, the cleaning process is to soak the loose block in deionized water to dissolve the CaCl2 salt, then collect the powder after filtering, and then wash and filter to further remove the CaCl2 salt. The above steps are repeated 3-5 times, and then the collected powder is dried at a drying temperature of 200-500°C and a drying time of 5h-10h. Finally, the dried powder is ground to obtain Mo-Si-B precursor powder.
[0018] In step 6, the precursor powder is sieved through 200-300 mesh and then hot pressed and sintered. During the sintering process, the vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 5-10℃ / min, the hot pressing sintering time is 3-5h, and the pressure is 35-45MPa.
[0019] The beneficial effects of the present invention are:
[0020] (1) The present invention adopts a molten salt method to prepare a Mo-Si-B precursor powder with small particle size, less agglomeration and low oxygen content, which effectively solves the key technical problems of easy oxidation and agglomeration of powder in the traditional powder metallurgy process, ensures that the Mo-Si-B alloy obtains a fine-grained structure with uniform three-phase distribution while greatly reducing the SiO2 content in the alloy, and provides new ideas and technical support for the preparation of high-strength and tough molybdenum alloys or other refractory metal-based alloys based on powder metallurgy technology.
[0021] (2) Compared with the traditional mechanical alloying technology, the molten salt method can effectively control the phase composition, particle size and grain size of the Mo-Si-B precursor powder by changing the calcination temperature and the salt-to-powder ratio, thereby making it easier to achieve the optimal design of the microstructure and performance of the Mo-Si-B alloy. At the same time, the method of the present invention has a simple process design, convenient operation, low cost, low equipment requirements, and is easy to achieve industrial production.
[0022] (3) The room temperature compressive strength of the Mo-Si-B alloy prepared by the present invention is 2850 MPa-2954 MPa, and the fracture toughness is 10.2-11.3 MPa·m 1 / 2 , which is superior to the compressive strength and fracture toughness of most of the Mo-Si-B alloys prepared by powder metallurgy, showing good comprehensive mechanical properties. The fine grain structure of the Mo-Si-B alloy has a significant strengthening and toughening effect, while the SiO2 content at the grain boundary is low, which improves the interface bonding of the alloy and reduces the probability of brittle fracture of the alloy when subjected to external loads. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope photograph of the fine-grained low-oxygen Mo-Si-B alloy prepared in Example 1. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method of the present invention is specifically implemented according to the following steps:
[0026] Step 1, ball-milling molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol to obtain a uniformly mixed slurry, wherein the solid powders can be mixed more uniformly in the liquid medium of anhydrous ethanol;
[0027] In step 1, molybdenum powder, silicon powder and boron powder are raw materials for preparing Mo-Si-B alloy, wherein the mass percentage of molybdenum powder is 93.0%-95.0%, the mass percentage of silicon powder is 4.0%-5.0%, and the mass percentage of boron powder is 1.0%-2.0%, and the sum of the above mass fractions is 100%; the purity of the molybdenum powder is ≥99.9%, and the particle size of the molybdenum powder is <5μm; the purity of the silicon powder is ≥99.99%, and the particle size of the silicon powder is <5μm; the boron powder is The purity is ≥99.95%, and the particle size of the boron powder is <1μm; the mass ratio of the CaCl2 salt to the total of molybdenum powder, silicon powder and boron powder is (1-2):1, the purity of the CaCl2 salt is ≥99.9%, and the particle size of the CaCl2 salt is <5μm; the volume of the anhydrous ethanol is 1 / 4-1 / 2 of the total volume of the molybdenum powder, silicon powder, boron powder and CaCl2 salt; in addition, the ball milling mixing adopts a planetary ball mill, and the ball milling jar and grinding balls used are all made of agate.
[0028] In step 1, the ball milling time is 6h-10h, the ball-to-material ratio is (1-2):1, the ball milling speed is 200r / min-400r / min, and Ar gas atmosphere is introduced during the ball milling process, and the gas pressure in the ball mill is 0.3MPa-0.6MPa.
[0029] Step 2, placing the mixed slurry obtained in step 1 in a vacuum atmosphere furnace to dry to obtain a mixed powder;
[0030] In step 2, the drying temperature is 200°C-500°C, and the drying time is 5h-10h.
[0031] Step 3: The mixed powder obtained in step 2 is firstly The cylindrical tableting mold is pressed into a powder tablet press. The small cylindrical green compact is then placed into In the tableting mold, fill the small cylinder with CaCl2 salt and press it again to form Large cylindrical green compact;
[0032] The pressure during the powder pressing process in step 3 is 25MPa to 37MPa.
[0033] Step 4, the large cylindrical pressed blank obtained in step 3 is placed in a vacuum tube furnace, heated and calcined from room temperature to obtain a loose block; in step 4, the pressed blank is heated from room temperature to 1000°C-1400°C, calcined for 1-2h, and then cooled to room temperature with the furnace to obtain a loose block. During the calcination process, a large amount of CaCl2 molten salt can effectively isolate oxygen, greatly reducing the oxygen content in the alloy powder. In addition, Mo, Si and B are mixed at the atomic scale under the liquid medium of the molten salt, and have a faster diffusion rate, so that the synthesis reaction is completed in a shorter time and at a lower temperature, and the molten salt runs through the generated powder particles, preventing the particles from connecting to each other, so that the dispersibility of the synthetic powder is very good, and it is easy to obtain a Mo-Si-B precursor powder with fine particles. The heating rate during the calcination process is 5-10°C / min, the vacuum degree in the furnace is ≤5Pa, and the calcination is completed. Cool to room temperature with the furnace.
[0034] Step 5: The loose block taken out after calcination is washed and filtered to remove CaCl2 salt, and then dried and ground to obtain Mo-Si-B precursor powder;
[0035] In step 5, the cleaning process is to soak the loose block in deionized water to dissolve the CaCl2 salt, then collect the powder after filtering through filter paper, and then wash and filter to further remove the CaCl2 salt. The above steps are repeated 3-5 times, and then the collected powder is placed in a vacuum atmosphere furnace for drying. The drying temperature is 200-500°C and the drying time is 5h-10h. Finally, the dried powder is ground in a mortar to obtain Mo-Si-B precursor powder.
[0036] Step 6: Place the Mo-Si-B precursor powder obtained in step 5 in a vacuum hot pressing sintering furnace and heat the temperature from room temperature to 1550-1700°C for hot pressing sintering. Then, reduce the pressure and cool it in the furnace before taking it out to obtain a fine-grained low-oxygen Mo-Si-B alloy.
[0037] In step 6, the precursor powder is screened with a 200-300 mesh Taylor sieve and then loaded into a graphite mold, and hot-pressed sintered in a vacuum hot-pressing furnace. During the sintering process, the vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 5-10℃ / min, the hot pressing sintering time is 3-5h, and the pressure is 35-45MPa.
[0038] The present invention is based on the preparation method of fine-grained low-oxygen molybdenum silicon boron alloy by molten salt method, firstly adopts molten salt method to prepare Mo-Si-B precursor powder, then vacuum hot presses and sinters the precursor powder to prepare Mo-Si-B bulk alloy. In the process of preparing the precursor powder, Mo, Si and B realize atomic-scale mixing under the liquid medium of CaCl2 molten salt, and have a faster diffusion rate, so that the synthesis reaction is completed in a shorter time and at a lower temperature. At the same time, the molten salt runs through the generated powder particles, preventing the interconnection between the particles, making the dispersibility of the synthetic powder very good, and the product after dissolution and washing has almost no agglomeration phenomenon. More importantly, the molten salt can effectively isolate oxygen and greatly reduce the oxygen content in the alloy powder. The above technical features can not only enable the Mo-Si-B alloy to obtain a fine-grained structure with uniform tissue distribution, but also reduce the oxygen impurities in the precursor powder by the shielding effect of the molten salt, thereby reducing the SiO2 content in the alloy, thereby optimizing the comprehensive mechanical properties of the alloy.
[0039] Example 1
[0040] A method for preparing a fine-grained low-oxygen Mo-Si-B alloy based on a molten salt method comprises the following steps:
[0041] Step 1, according to the Mo-12Si-8.5B (at.%) alloy composition, weigh 142.02g, 6.27g and 1.71g of molybdenum powder, silicon powder and boron powder respectively, with respective mass percentages of 94.68wt%, 4.18wt% and 1.14wt% respectively; weigh 150g of CaCl2 salt; and measure 30ml of anhydrous ethanol. First, molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol are ball-milled and mixed into slurry in a planetary ball mill, wherein the ball milling time is 6h, the ball-to-material ratio is 1:1, the ball mill speed is 250r / min, and the Ar gas pressure filled in the ball mill tank is 0.3MPa;
[0042] Step 2, drying the mixed slurry in a vacuum furnace at 500° C. for 5 h to obtain a mixed powder;
[0043] Step 3: The mixed powder obtained in step 2 is firstly The cylindrical tableting mold is pressed into a powder tablet press. The small cylindrical green compact is then placed into In the tableting mold, fill the small cylindrical green body with CaCl2 salt and press it again. The large cylindrical green compact, the pressure of the powder tablet press is 25MPa;
[0044] Step 4, placing the large cylindrical green compact into an alumina crucible and placing them together in a vacuum tube furnace for calcination, the calcination temperature is 1400°C, the holding time is 2h, the heating rate is 5°C / min, the vacuum degree in the furnace is ≤5Pa, and after the calcination is completed, the green compact is cooled to room temperature with the furnace to obtain a loose block;
[0045] Step 5, washing and filtering the calcined loose block three times, and then drying it in a vacuum furnace at 500° C. for 5 hours. Finally, the dried powder is ground to obtain a precursor powder.
[0046] Step 6: The precursor powder is sieved through a 200-mesh Taylor sieve and then hot-pressed in a vacuum hot-pressing sintering furnace. The vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 5℃ / min, the sintering temperature is 1600℃, the sintering time is 3h, the pressure is 35MPa, and after sintering, the fine-grained low-oxygen Mo-12Si-8.5B alloy is obtained by cooling to room temperature with the furnace.
[0047] Figure 1 is a scanning electron microscope photograph of the fine-grained low-oxygen Mo-12Si-8.5B alloy prepared in this embodiment. Figure 1 It can be seen that the microstructure of the alloy is characterized by isolated island-shaped α-Mo dispersed on a continuous Mo3Si and Mo5SiB2 matrix, and the three phases are evenly distributed. The grain and particle sizes of the alloy are in the submicron to micron range. The content of SiO2 particles at the grain boundary is only 2.14 vol.%. The room temperature compressive strength of the alloy is measured to be 2850 MPa, and the fracture toughness of the alloy is 11.3 MPa·m 1 / 2 .
[0048] Comparative Example 1
[0049] The method for preparing the Mo-Si-B alloy in this comparative example comprises the following steps:
[0050] Step 1, according to the Mo-12Si-8.5B (at.%) alloy composition, weigh 142.02g, 6.27g and 1.71g of molybdenum powder, silicon powder and boron powder, respectively, with respective mass percentages of 94.68wt%, 4.18wt% and 1.14wt%, respectively. The molybdenum powder, silicon powder and boron powder are ball-milled and mixed in a planetary ball mill, wherein the ball mill and the grinding balls are made of agate, the ball milling time is 6h, the ball-to-material ratio is 1:1, the speed of the ball mill is 250r / min, and the Ar gas pressure filled in the ball mill is 0.3MPa;
[0051] Step 2: Place the mixed powder into a high-energy ball mill for mechanical alloying treatment to obtain Mo-Si-B precursor powder, wherein the ball mill and grinding balls are made of tungsten carbide, the ball-to-material ratio is 10:1, the time is 15 hours, the speed of the ball mill is 250 r / min, and the Ar gas pressure filled in the ball mill is 0.3 MPa.
[0052] Step 3: The precursor powder is sieved through a 200-mesh Taylor sieve and then hot-pressed and sintered in a vacuum hot-pressing sintering furnace. The vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 5℃ / min, the sintering temperature is 1600℃, the sintering time is 3h, the pressure is 35MPa, and the Mo-12Si-8.5B alloy is obtained by cooling to room temperature with the furnace after sintering.
[0053] The grain and particle size of the Mo-12Si-8.5B alloy in this comparative example are both in the submicron to micron range. The content of SiO2 particles at the grain boundary is 7.6 vol.%. The room temperature compressive strength of the alloy is 2775 MPa, and the fracture toughness of the alloy is 8.52 MPa·m 1 / 2 .
[0054] The results of Example 1 and Comparative Example 1 show that the compressive strength and fracture toughness of the Mo-Si-B alloy prepared by the molten salt method of the present invention are improved compared with the Mo-Si-B alloy prepared by mechanical alloying, which is not only related to the uniform fine-grained microstructure, but also to the less SiO2 in the alloy.
[0055] Example 2
[0056] A method for preparing a fine-grained low-oxygen Mo-Si-B alloy based on a molten salt method comprises the following steps:
[0057] Step 1, according to the Mo-13Si-11B (at.%) alloy composition, weigh 140.67g of molybdenum powder, 7.05g of silicon powder and 2.28g of boron powder, with respective mass percentages of 93.78wt%, 4.70wt% and 1.52wt%, respectively. Weigh 225g of CaCl2 salt; measure 40ml of anhydrous ethanol. First, molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol are ball-milled and mixed into slurry in a planetary ball mill, wherein the ball milling time is 7h, the ball-to-material ratio is 1.2:1, the speed of the ball mill is 300r / min, and the Ar gas pressure filled in the ball mill tank is 0.4MPa;
[0058] Step 2, drying the mixed slurry in a vacuum furnace at 350° C. for 8 h to obtain a mixed powder;
[0059] Step 3: The mixed powder obtained in step 2 is firstly The cylindrical tableting mold is pressed into a powder tablet press. The small cylindrical green compact is then placed into In the tableting mold, fill the small cylindrical green body with CaCl2 salt and press it again. The large cylindrical green compact, the pressure of the powder tablet press is 30MPa;
[0060] Step 4, placing the large cylindrical green compact into an alumina crucible and placing them together in a vacuum tube furnace for calcination, the calcination temperature is 1100° C., the holding time is 1 h, the heating rate is 8° C. / min, the vacuum degree in the furnace is ≤5 Pa, and after the calcination is completed, the green compact is cooled to room temperature with the furnace to obtain a loose block;
[0061] Step 5, washing and filtering the calcined loose block four times, and then drying it in a vacuum furnace at 350° C. for 8 hours. Finally, the dried powder is ground to obtain a precursor powder.
[0062] Step 6: The precursor powder is sieved through a 200-mesh Taylor sieve and then hot-pressed in a vacuum hot-pressing sintering furnace. The vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 8℃ / min, the sintering temperature is 1550℃, the sintering time is 4h, the pressure is 35MPa, and after sintering, it is cooled to room temperature with the furnace to obtain a fine-grained low-oxygen Mo-13Si-11B alloy.
[0063] The microstructure of the fine-grained low-oxygen Mo-13Si-11B alloy prepared in this embodiment is characterized by isolated island-shaped α-Mo dispersed on a continuous Mo3Si and Mo5SiB2 matrix, and the three phases are evenly distributed. The grain and particle sizes of the alloy are in the submicron to micron range. The content of SiO2 particles at the grain boundary is only 2.22 vol.%. The room temperature compressive strength of the alloy is measured to be 2882 MPa, and the fracture toughness of the alloy is 11.0 MPa·m 1 / 2 .
[0064] Example 3
[0065] A method for preparing a fine-grained low-oxygen Mo-Si-B alloy based on a molten salt method comprises the following steps:
[0066] Step 1, according to the Mo-12Si-13B (at.%) alloy composition, weigh 140.67g, 6.585g and 2.745g of molybdenum powder, silicon powder and boron powder respectively, and their mass percentages are 93.78wt%, 4.39wt% and 1.83wt% respectively. Weigh 150g of CaCl2 salt; measure 30ml of anhydrous ethanol. First, molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol are ball-milled and mixed into slurry in a planetary ball mill, wherein the ball milling time is 9h, the ball-to-material ratio is 1.5:1, the speed of the ball mill is 300r / min, and the Ar gas pressure filled in the ball mill tank is 0.45MPa;
[0067] Step 2, drying the mixed slurry in a vacuum furnace at 400° C. for 7 h to obtain a mixed powder;
[0068] Step 3: The mixed powder obtained in step 2 is firstly The cylindrical tableting mold is pressed into a powder tablet press. The small cylindrical green compact is then placed into In the tableting mold, fill the small cylindrical green body with CaCl2 salt and press it again. The large cylindrical green compact, the pressure of the powder tablet press is 31MPa;
[0069] Step 4, placing the large cylindrical green compact into an alumina crucible and placing them together in a vacuum tube furnace for calcination, the calcination temperature is 1100°C, the holding time is 2h, the heating rate is 10°C / min, the vacuum degree in the furnace is ≤5Pa, and after the calcination is completed, the green compact is cooled to room temperature with the furnace to obtain a loose block;
[0070] Step 5, the calcined loose block is washed and filtered for 5 times, and then placed in a vacuum atmosphere furnace for drying at a temperature of 400° C. for 7 hours. Finally, the dried powder is ground to obtain a precursor powder.
[0071] Step 6: The precursor powder is sieved through a 300-mesh Taylor sieve and then hot-pressed and sintered in a vacuum hot-pressing sintering furnace. The vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 10℃ / min, the sintering temperature is 1650℃, the sintering time is 3.5h, the pressure is 40MPa, and after sintering, it is cooled to room temperature with the furnace to obtain a fine-grained low-oxygen Mo-12Si-13B alloy.
[0072] The microstructure of the fine-grained low-oxygen Mo-12Si-13B alloy prepared in this embodiment is characterized by isolated island-shaped α-Mo dispersed on a continuous Mo3Si and Mo5SiB2 matrix, and the three phases are evenly distributed. The grain and particle sizes of the alloy are in the submicron to micron range. The content of SiO2 particles at the grain boundary is only 2.32 vol.%. The room temperature compressive strength of the alloy is measured to be 2954 MPa, and the fracture toughness of the alloy is 10.2 MPa·m 1 / 2 .
[0073] Example 4
[0074] A method for preparing a fine-grained low-oxygen Mo-Si-B alloy based on a molten salt method comprises the following steps:
[0075] Step 1, according to the Mo-11Si-14B (at.%) alloy composition, weigh 140.98g, 6.06g and 2.96g of molybdenum powder, silicon powder and boron powder respectively, and their mass percentages are 93.99wt%, 4.04wt% and 1.97wt% respectively. Weigh 225g of CaCl2 salt; measure 40ml of anhydrous ethanol. First, molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol are ball-milled and mixed into slurry in a planetary ball mill, wherein the ball milling time is 9h, the ball-to-material ratio is 1.5:1, the speed of the ball mill is 350r / min, and the Ar gas pressure filled in the ball mill tank is 0.5MPa;
[0076] Step 2, drying the mixed slurry in a vacuum furnace at 450° C. for 6 h to obtain a mixed powder;
[0077] Step 3: The mixed powder obtained in step 2 is firstly The cylindrical tableting mold is pressed into a powder tablet press. The small cylindrical green compact is then placed into In the tableting mold, fill the small cylindrical green body with CaCl2 salt and press it again. The large cylindrical green compact, the pressure of the powder tablet press is 35MPa;
[0078] Step 4, placing the large cylindrical green compact into an alumina crucible and placing them together in a vacuum tube furnace for calcination, the calcination temperature is 1400°C, the holding time is 1h, the heating rate is 10°C / min, the vacuum degree in the furnace is ≤5Pa, and after the calcination is completed, the green compact is cooled to room temperature with the furnace to obtain a loose block;
[0079] Step 5, washing and filtering the calcined loose block four times, and then drying it in a vacuum furnace at 450° C. for 6 hours. Finally, the dried powder is ground to obtain a precursor powder.
[0080] Step 6: The precursor powder is sieved through a 300-mesh Taylor sieve and then hot-pressed and sintered in a vacuum hot-pressing sintering furnace. The vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 10℃ / min, the sintering temperature is 1650℃, the sintering time is 3h, the pressure is 45MPa, and after sintering, it is cooled to room temperature with the furnace to obtain a fine-grained low-oxygen Mo-11Si-14B alloy.
[0081] The microstructure of the fine-grained low-oxygen Mo-11Si-14B alloy prepared in this embodiment is characterized by isolated island-shaped α-Mo dispersed on a continuous Mo3Si and Mo5SiB2 matrix, and the three phases are evenly distributed. The grain and particle sizes of the alloy are in the submicron to micron range. The content of SiO2 particles at the grain boundary is only 2.28 vol.%. The room temperature compressive strength of the alloy is measured to be 2867 MPa, and the fracture toughness of the alloy is 10.7 MPa·m 1 / 2 .
[0082] Example 5
[0083] A method for preparing a fine-grained low-oxygen Mo-Si-B alloy based on a molten salt method comprises the following steps:
[0084] Step 1, according to the Mo-12Si-12B (at.%) alloy composition, weigh 140.97g, 6.525g and 2.505g of molybdenum powder, silicon powder and boron powder respectively, and their mass percentages are 93.98wt%, 4.35wt% and 1.67wt% respectively. Weigh 300g of CaCl2 salt; measure 50ml of anhydrous ethanol. First, molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol are ball-milled and mixed into slurry in a planetary ball mill, wherein the ball milling time is 10h, the ball-to-material ratio is 2:1, the speed of the ball mill is 400r / min, and the Ar gas pressure filled in the ball mill tank is 0.6MPa;
[0085] Step 2, drying the mixed slurry in a vacuum furnace at 500° C. for 5 h to obtain a mixed powder;
[0086] Step 3: The mixed powder obtained in step 2 is firstly The cylindrical tableting mold is pressed into a powder tablet press. The small cylindrical green compact is then placed into In the tableting mold, fill the small cylindrical green body with CaCl2 salt and press it again. The large cylindrical green compact, the pressure of the powder tablet press is 37MPa;
[0087] Step 4, placing the large cylindrical green compact into an alumina crucible and placing them together in a vacuum tube furnace for calcination, the calcination temperature is 1400°C, the holding time is 2h, the heating rate is 10°C / min, the vacuum degree in the furnace is ≤5Pa, and after the calcination is completed, the green compact is cooled to room temperature with the furnace to obtain a loose block;
[0088] Step 5, washing and filtering the calcined loose block repeatedly for 5 times, and then drying it in a vacuum atmosphere furnace at a temperature of 500° C. for 5 hours. Finally, the dried powder is ground to obtain a precursor powder.
[0089] Step 6: The precursor powder is sieved through a 300-mesh Taylor sieve and then hot-pressed and sintered in a vacuum hot-pressing sintering furnace. The vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 10℃ / min, the sintering temperature is 1650℃, the sintering time is 3h, the pressure is 45MPa, and after sintering, it is cooled to room temperature in the furnace to obtain a fine-grained low-oxygen Mo-12Si-12B alloy.
[0090] The microstructure of the fine-grained low-oxygen Mo-12Si-12B alloy prepared in this embodiment is characterized by isolated island-shaped α-Mo dispersed on a continuous Mo3Si and Mo5SiB2 matrix, and the three phases are evenly distributed. The grain and particle sizes of the alloy are in the submicron to micron range. The content of SiO2 particles at the grain boundary is only 2.35 vol.%. The room temperature compressive strength of the alloy is measured to be 2902 MPa, and the fracture toughness of the alloy is 10.5 MPa·m 1 / 2 .
Claims
1. A method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method, characterized in that: Follow the steps below to implement it: Step 1, ball-milling molybdenum powder, silicon powder, boron powder, CaCl2 salt and anhydrous ethanol to obtain a uniformly mixed slurry; Step 2, drying the mixed slurry obtained in step 1 to obtain a mixed powder; Step 3: Press the mixed powder obtained in step 2 into The small cylindrical green compact is then placed into In the tableting mold, fill the small cylinder with CaCl2 salt and press it again to form Large cylindrical green compact; Step 4: heating and calcining the large cylindrical compact obtained in step 3 from room temperature to obtain a loose block; Step 5: The loose block taken out after calcination is washed and filtered to remove CaCl2 salt, and then dried and ground to obtain Mo-Si-B precursor powder; Step 6: The Mo-Si-B precursor powder obtained in step 5 is heated from room temperature to 1550-1700° C. and then hot-pressed and sintered. The powder is then depressurized and cooled in the furnace before being taken out to obtain a fine-grained low-oxygen Mo-Si-B alloy.
2. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: In the step 1, the mass percentage of molybdenum powder is 93.0%-95.0%, the mass percentage of silicon powder is 4.0%-5.0%, and the mass percentage of boron powder is 1.0%-2.0%, and the sum of the above mass fractions is 100%; the purity of the molybdenum powder is ≥99.9%, and the particle size of the molybdenum powder is <5μm; the purity of the silicon powder is ≥99.99%, and the particle size of the silicon powder is <5μm; the purity of the boron powder is ≥99.95%, and the particle size of the boron powder is <1μm; the mass ratio of the CaCl2 salt to the total of the molybdenum powder, silicon powder and boron powder is (1-2): 1, the purity of the CaCl2 salt is ≥99.9%, and the particle size of the CaCl2 salt is <5μm; the volume of the anhydrous ethanol is 1 / 4-1 / 2 of the total volume of the molybdenum powder, silicon powder, boron powder and CaCl2 salt.
3. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: In step 1, the ball milling time is 6h-10h, the ball-to-material ratio is (1-2):1, the ball milling speed is 200r / min-400r / min, and Ar gas atmosphere is introduced during the ball milling process, and the gas pressure in the ball mill is 0.3MPa-0.6MPa.
4. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: In step 2, the drying temperature is 200° C.-500° C., and the drying time is 5 h-10 h.
5. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: The pressure during the powder pressing process in step 3 is 25 MPa to 37 MPa.
6. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: In step 4, the material is heated from room temperature to 1000°C-1400°C, calcined for 1-2 hours, and then cooled to room temperature in the furnace to obtain a loose block. The heating rate during the calcination process is 5-10°C / min, the vacuum degree in the furnace is ≤5Pa, and the material is cooled to room temperature in the furnace after the calcination.
7. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: The cleaning process in step 5 is to soak the loose block in deionized water to dissolve the CaCl2 salt, then collect the powder after filtering, and then wash and filter to further remove the CaCl2 salt. The above steps are repeated 3-5 times, and then the collected powder is dried at a drying temperature of 200-500°C and a drying time of 5h-10h. Finally, the dried powder is ground to obtain Mo-Si-B precursor powder.
8. The method for preparing a fine-grained low-oxygen molybdenum-silicon-boron alloy based on a molten salt method according to claim 1, characterized in that: In step 6, the precursor powder is sifted through 200-300 mesh and then hot pressed and sintered. During the sintering process, the vacuum degree is maintained at 6×10 -3 Pa to 1.5×10 -2 Pa, the heating rate is 5-10℃ / min, the hot pressing sintering time is 3-5h, and the pressure is 35-45MPa.
Citation Information
Patent Citations
Method for preparing molybdenum-silicium-boron alloy
CN101397613A
Preparation method for high-temperature-resistant Mo-Si-B alloy
CN103160701A